2008
DOI: 10.1111/j.1365-2222.2008.03065.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there an in vitro test for type IV allergy discriminating between sensitization and allergic disease?

Abstract: Contact dermatitis is defined as an inflammatory response of the upper layers of the skin -namely epidermis and dermis -that occurs as a result of contact with exogenous substances. It accounts for approximately 80% of environment/occupation-based dermatoses and 30% of all occupational diseases [1].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Although previous studies have suggested that the ACD response might be attenuated in patients with AD, 25,27 these studies focused on immune responses in peripheral blood, which might not be representative of skin, [43][44][45][46] or on clinically irrelevant sensitizers, such as DNCB. 27 Recently, Newell et al 26 demonstrated an attenuated hypersensitivity reaction and T H 2 skewing in nonlesional AD versus healthy skin by using a strong hapten (DNCB), suggesting that the characteristic immune phenotype of background AD skin contributes to the distinct T H 2 polarization on challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested that the ACD response might be attenuated in patients with AD, 25,27 these studies focused on immune responses in peripheral blood, which might not be representative of skin, [43][44][45][46] or on clinically irrelevant sensitizers, such as DNCB. 27 Recently, Newell et al 26 demonstrated an attenuated hypersensitivity reaction and T H 2 skewing in nonlesional AD versus healthy skin by using a strong hapten (DNCB), suggesting that the characteristic immune phenotype of background AD skin contributes to the distinct T H 2 polarization on challenge.…”
Section: Discussionmentioning
confidence: 99%
“…For nearly 120 years [1] the largely unchanged patch test has remained the “gold standard” for detecting delayed hypersensitivity in diagnosing allergic contact dermatitis. In‐vitro tests have not yet been sufficiently evaluated for routine clinical use [87, 88].…”
Section: In‐vitro Testsmentioning
confidence: 99%
“…In consequence, the combination of clinical history and patch test results continues to be the basis for the diagnosis of ACD [17]. Further studies are needed in search of an innovative in vitro test method with sufficient discrimination between allergic and non-allergic patients [26].…”
Section: Resultsmentioning
confidence: 99%
“…However, we omitted staining with anti-CD45ROFITC due to a too high restriction resulting in a small number of analyzable T cells. Second, it is reported that nickel sulfate has in contrast to other metal salts non-specific stimulatory properties in vitro which still is a major problem [14,15,17]. In our study we obtained the raw material of nickel sulfate hexahydrate straight from the production process of the patch test substance and the highest concentration used for stimulation was 2.6 μg/ml [14].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation